Peroxisome Proliferator-Activated Receptor Gamma Polymorphisms and Coronary Heart Disease - Jean Dallongeville; Carlos Iribarren; Jean Ferrières; Liisa Lyon; Alun Evans; Alan S. Go; Dominique Arveiler; Stephen P. Fortmann; Pierre Ducimetière; Mark A. Hlatky; Philippe Amouyel; Audrey Southwick; et al. (PPAR Research)
Single nucleotide polymorphisms (SNPs) in the peroxisome proliferator-activated receptor γ (PPARG) gene have been associated with cardiovascular risk factors, particularly obesity and diabetes. We assessed the relationship between 4 PPARG SNPs (C-681G, C-689T, Pro12Ala, and C1431T) and coronary heart disease (CHD) in the PRIME (249 cases/494 controls, only men) and ADVANCE (1,076 cases/805 controls, men or women) studies. In PRIME, homozygote individuals for the minor allele of the PPARG C-689T, Pro12Ala, and C1431T SNPs tended to have a higher risk of CHD than homozygote individuals for the frequent allele (adjusted OR [95% CI] = 3.43 [0.96–12.27], P=.058, 3.41 [0.95–12.22], P=.060 and 5.10 [0.99–26.37], P=.050, resp.). No such association could be detected in ADVANCE. Haplotype distributions were similar in cases and control in both studies. A meta-analysis on the Pro12Ala SNP, based on our data and 11 other published association studies (6,898 CHD cases/11,287 controls), revealed that there was no evidence for a significant association under the dominant model (OR=0.99 [0.92–1.07], P=.82). However, there was a borderline association under the recessive model (OR=1.29 [0.99–1.67], P=.06) that became significant when considering men only (OR=1.73 [1.20–2.48], P=.003). In conclusion, the PPARG Ala12Ala genotype might be associated with a higher CHD risk in men but further confirmation studies are needed.